The Corsini Encyclopedia of Psychology 2010
DOI: 10.1002/9780470479216.corpsy0982
|View full text |Cite
|
Sign up to set email alerts
|

Terrorism

Abstract: Terrorism is defined in Title 22 of the U.S. Code, Section 2656f(d), as “premeditated, politically motivated violence perpetrated against noncombatant targets by sub‐national groups … intended to influence an audience.” Risk analyses suggest that the target locations for terrorist attacks are typically those that are critical to the government and economy, contain iconic symbols, and are high in human occupancy. These targets tend to exist in major urban areas, and thus when terrorism strikes, a great many ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The three textbooks with the greatest number of keyword mentions were by Hooley et al (2020; n = 508), Nevid et al (2021; n = 321), and Kring and Johnson (2021; n = 313). The three textbooks with the greatest number of citations were by Hooley et al (2020; n = 316), Comer and Comer (2021; n = 174), and Kring and Johnson (2021; n = 134). See the total number of keyword and citation mentions in Table 1…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The three textbooks with the greatest number of keyword mentions were by Hooley et al (2020; n = 508), Nevid et al (2021; n = 321), and Kring and Johnson (2021; n = 313). The three textbooks with the greatest number of citations were by Hooley et al (2020; n = 316), Comer and Comer (2021; n = 174), and Kring and Johnson (2021; n = 134). See the total number of keyword and citation mentions in Table 1…”
Section: Resultsmentioning
confidence: 98%
“…Nevid et al’s (2021) textbook displayed the widest breadth of linkage between childhood trauma and psychopathology, connecting childhood trauma to 93% of the identified DSM-5 diagnostic categories (see Table 3). In contrast, the textbooks by Durand et al (2018) and Comer and Comer (2021) each linked child trauma to only 73% of the identified diagnostic categories. Consistent with the findings from Wilgus et al (2016), Nevid et al’s (2021) textbook provided the greatest breadth of coverage about trauma-related psychopathology.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Abnormal Psychology is the name still given to the study of mental illness by many Psychology degree courses (Hooley et al , 2016; Comer and Comer, 2021). Only a few textbooks have managed to escape this terminology, most notably the excellent textbook by John Cromby, David Harper and Paula Reavey, “Psychology, Mental Health and Distress”, (Cromby et al , 2013).…”
Section: Introductionmentioning
confidence: 99%